Lamiaceae Species: Biology, Ecology and Practical Uses - Stankovic, Milan (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This Special Issue Book entitled ""Lamiaceae Species: Biology, Ecology and Practical Uses"" contributes to the knowledge of selected Lamiaceae species from several perspectives, such as diversity and phytogeography, taxonomy, ethnobotany, and quantitative and qualitative composition, as well as the biological activity of secondary metabolites.